$\begin{array}{1 1}(A)\;\large\frac{2}{3}&(B)\;\large\frac{1}{3}\\(C)\;\large\frac{-1}{3}&(D)\;\large\frac{-2}{3}\end{array} $

Let the roots be $\alpha,2\alpha$

$(\alpha(2\alpha)=\large\frac{2}{a^2-5a+3}$$\Rightarrow \alpha^2=\large\frac{1}{a^2-5a+3}$

$\alpha+2\alpha=3\alpha=-\large\frac{-(3a-1)}{a^2-5a+3}$

$\Rightarrow 3\alpha=(1-3a)\alpha^2\Rightarrow \alpha=\large\frac{3}{1-3a}$

$2\alpha=\large\frac{6}{1-3a}$

$\alpha^2=\large\frac{9}{(1-3a)^2}=\frac{1}{a^2-5a+3}$

$\Rightarrow 9a^2-45a+27=9a^2-6a+1$

$\Rightarrow 26=39a\Rightarrow a=\large\frac{2}{3}$

Hence (A) is the correct answer.

Ask Question

Tag:MathPhyChemBioOther

Take Test

...